INDEPENDENCE, WAR AND DIPLOMACY: MEXICO AND SPAIN IN THE INTERNATIONAL CONTEXT, 1821-1830 (Tzintzun, Revista de Estudios Históricos, 2024)
The disintegration of the Spanish empire, and the Spanish Americanindependence processes, altered power relations in the Atlantic world, triggeringinternational competition over resources and trade in the American territoriesof the former Spanish empire. The international scene, then dominated by themonarchies that formed the Holy Alliance –Russia, Prussia, Austria, France–, byGreat Britain and by the United States, thus became a major factor in the courseand outcome of the conflict between Spain and its former colonial possessions.The aim of this text is to analyze this international context, based on the diplomaticaction of world powers, with special emphasis on the United States and England,and evaluate the weight it had in the conflictive informal relations that wereestablished between Spain and the newly independent Mexican nation, between1821 and 1830.
Keywords: Mexican Independence; Spain-Mexico Relations; International Context; nternational Diplomacy